Gene polymorphisms and serum levels of mannose-binding lectin in Czech patients with recurrent aphthous stomatitis: A case-control study - Izakovicova, Pavla; Slezakova, Simona; Jiraskova Zakostelska, Zuzana; Sistkova, Jana; Mlcuchova, Natalie; Bartova, Jirina; Petanova, Jitka; Kuklinek, Pavel; Fassmann, Antonin; Dusek, Ladislav; Izakovicova Holla, Lydie; Borilova Linhartova, Petra (Journal of oral pathology & medicine, 2023)
BACKGROUND: Recurrent aphthous stomatitis is one of the most prevalent oral mucosal immunological diseases. A recent case-control study in the Egyptian population suggested that single nucleotide polymorphism Gly54Asp (rs1800450) of the mannose-binding lectin 2 gene might affect the mannose-binding lectin serum level and recurrent aphthous stomatitis development. The aim of this study was to determine the distribution of six functional mannose-binding lectin 2 gene polymorphisms and analyse their role in recurrent aphthous stomatitis susceptibility in the Czech population. METHODS: The study included 227 subjects; 137 healthy people and 90 patients with recurrent aphthous stomatitis. Six mannose-binding lectin 2 gene polymorphisms (rs11003125, rs7096206, rs7095891, rs5030737, rs1800450, rs1800451) were analysed by the SNaPshot assay method, mannose-binding lectin serum levels were determined by enzyme-linked immunosorbent assay (ELISA) method in a subgroup of subjects (N = 87). RESULTS: No significant differences in mean of mannose-binding lectin serum levels between healthy controls and patients with recurrent aphthous stomatitis were observed (383 ng/ml ± 249 standard deviation (SD) vs. 316 ng/ml ± 177 SD in remission phase vs. 343 ng/ml ± 254 SD in active phase; p > 0.05), also the allele and genotype frequencies of the studied mannose-binding lectin 2 polymorphisms did not differ significantly between the two groups (p > 0.05, odds ratio (OR): 0.75-1.23). Moreover, the distribution of mannose-binding lectin 2 haplotypes and haplogenotypes was similar in the healthy subjects and patients with recurrent aphthous stomatitis (p > 0.05, OR: 0.75-1.23). CONCLUSIONS: This study did not confirm the previously reported association of the mannose-binding lectin 2 Gly54Asp gene variant and low mannose-binding lectin serum level as the risk factors for susceptibility to recurrent aphthous stomatitis. In addition, no significant relationships between mannose-binding lectin 2 functional haplotypes or haplogenotypes and recurrent aphthous stomatitis were observed.
Keywords: polymorphism; genetická predispozice k nemoci; Czech Republic; Gene Frequency; Humans; Mannose-Binding Lectin; Genotype; Genetic Predisposition to Disease; Polymorphism, Single Nucleotide; lidé; jednonukleotidový polymorfismus; aftózní stomatitida; Česká republika; haplogenotype; haplotype; studie případů a kontrol; Case-Control Studies; genotyp; lektin vázající mannosu; frekvence genu; recurrent aphthous stomatitis; MBL; Stomatitis, Aphthous